KEBIJAKAN DEPORTASI ISRAEL TERHADAP PENDATANG ILEGAL BERKEBANGSAAN AFRIKA - Geraldio B, Rhafa Jireh; Darmiasih, D. A. Wiwik; Suwecawangsa, Putu Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT   The issue of refugees is an issue that continues to grow and has significant impact on a country. A state has the ability to deport refugees in their country. Israel has decided to deport African refugees who are predominantly Eritrean and Sudanese. The Deportation policy of Israel was carried out after the number of refugees from Africa in the country continued to grow. Israel sees African refugees coming illegally to their country. The Refugees who came also received negative responses due to the impact they caused inside Israel. This research analyzes the reasons of Israel’s deportation policy towards African refugees. The data is collected from various network sites, scientific research, journals, news, and articles related to this research. The concept uses is National Security and Securitization. This research focuses on Israel’s decision to create a deportation policy to secure its national security from African refugees residing in its country.   Keywords: Israel’s deportation policy, African refugees, Security